Immigrants' 'Ability' and Welfare as a Function of Cultural Diversity: Effect of Cultural Capital at Individual and Local Level - Annie Tubadji; Masood Gheasi; Peter Nijkamp (Institute for the Study of Labor (IZA), 2014)
This paper presents an operationalization of a mixed BourdieuMincer-type model that seeks to find evidence for individual and local cultural capital effects on human capital 'ability'. We aim to compare these effects for native workers and immigrants (as well as between immigrants themselves) in a locality. The main objective of the paper is twofold: 1) to examine how ethnic background affects immigrants' schooling results; and 2) to explore the link between the wage differential of immigrant young workers entering the labour market in the context of a locally varying cultural milieu. Our study utilises the 20072009 data set for higher professional education (termed HBO in Dutch) graduates from Maastricht University. We use a two-stage least squares (2SLS) estimation method to analyse empirically a system of two equations. In the first Bourdieu-type equation, individual cultural capital, together with school type/quality, explains the individual's schooling achievement. Next, this 'schooling achievement' is employed as an explanatory variable in the second Mincer-type equation, which examines wage differential effects. Our Mincer-type equation is next augmented with a control for the local cultural milieu. We find evidence of ethnic segregation with regard to the quality of educational institution to which immigrants have access, which naturally explains part of the wage differential effect. Moreover, we find that local cultural capital determines the size of the wage gap.
Keywords: Z10; O31; O43; R11; 330; immigration; wage differential; cultural capital; local cultural milieu; Mincer equation